Epidemiological Screening And Genotyping Analysis Of Hepatitis C Virus In Jazan Region, Saudi Arabia (Journal of Namibian Studies : History Politics Culture, 2024)
Globally, HCV infection is a significant public health concern leading to chronic liver disease (cirrhosis, hepatocellular carcinoma) resulting in substantial morbidity and mortality. HCV genotyping is the primary tool for clinical evaluation, disease pathogenesis, treatment, and follow-up of infected cases. The variations in HCV genotype prevalence present challenges to developing vaccines and therapeutics. To identify the distribution of HCV genotypes and subtypes in the Jazan region, a hospital-based prospective study was conducted. A total of 52 HCV clinically infected patients that had previously been positively tested by ELISA were randomly selected and were subjected to genotyping analysis and liver biochemical marker function test. GT-4 and GT-1 were predominated in Jazan region with the highest infection rates observed in adults between 26-65 years old who are married and of Saudi nationality. Relatively, no significant difference between other demographic factors tested.  The biochemical markers tested suggest liver dysfunction with elevated albumin, bilirubin, ALP, and ALT levels. Therefore, our results may require further investigation to determine the underlying cause of the liver abnormalities.